Literature Reviews of Topology Optimal Design Methods and Applications in Magnetic Devices - Jiaqi Wu; Ziyan Ren; Dianhai Zhang (Energies)
With the evolution of magnetic devices toward structural innovation and high reliability, the traditional design methods, such as size optimization and shape optimization, are limited by preset structural forms, making it challenging to generate novel structures and topologies. Topology-optimized design methods can achieve an optimal distribution of constituent materials of magnetic devices by optimizing the objective performance subject to certain constraints, and can provide greater freedom for designers. Based on the above background, this paper firstly investigates the principles of deterministic topology optimization methods, and introduces the latest specific applications in magnetic devices. It also demonstrates the advantages of topology optimization technology in enhancing operating performance, fostering structural innovation, and improving material utilization in magnetic devices. To manage uncertainties in design and manufacturing processes of magnetic devices, this paper analyzes uncertainty topology optimization methods, respectively, reliability and robustness-based topology optimization algorithms. To facilitate manufacturing, this paper summarizes the filter strategy for the new structure obtained by topology optimization. Finally, the problems faced by the topology optimization method in the field of magnetic devices are discussed, and a future development direction is projected.